IDENTIFICATION OF TETA AND OPRL GENES OF PSUEDOMONAS AERUGINOSA ISOLATED FROM DIABETICFOOT ULCER’S PATIENTS FROM SELECTED AREAS OF PUNJAB (The Research of Medical Science Review, 2025)
Diabetic Foot Ulcer poses a critical concern for healthcare organizations concerning diabetes. This issue presents a significant medical hurdle due to the widespread occurrence of bacterial infections that are resistant to multiple drugs. Among the various pathogens linked to Diabetic Foot Ulcers (DFUs), Pseudomonas aeruginosa stands out as a prevalent one, known for its resistance to multiple types of antibiotics. This research aims to analyze the prevalence of oprL and tetA genes in drug resistant strains of P. aeruginosa isolated from DFU’s samples. These strains have been sourced from DFUs patients admitted in different hospitals of Punjab region. The study's dataset consists of 100 pus samples collected from individuals afflicted by diabetes and experiencing foot ulcers. All pus samples were cultured on cetrimide agar and further confirmed by different biochemical tests, then antibiotic susceptibility test was performed. Out of 100 samples, 25 were positive for P. aeruginosa. P. aeruginosa showed 100% resistance to ampicillin followed by tetracycline (74%), erythromycin (52%), gentamycin (69.7%), ceftazidime (24%), imipenem (44%), and ciprofloxacin (20%). Total 16 (69%) isolates of the P. aeruginosa showed multidrug resistance (MDR). The moleculer identification of genes in drug resistant isolates of P. aeruginosa was achieved using oprLand tetA primers. DNA Extraction and PCR analysis confirmed the presence of oprLand tetA genes in P. aeruginosa. Out of 25 (100%) isolated bacterial strains, oprL gene was identified in 23(92%) bacterial isolates followed by tetA gene that was detected in 21(84%) isolated strains of P. aeruginosa. From 21(84%) isolates in which tetA gene was detected, almost 15(68%) were tetracycline resistant. The findings from this study might contribute to a better understanding of the resistance mechanisms of P. aeruginosa in DFUs, facilitating the development of targeted therapeutic approaches and effective antimicrobial stewardship programs.